Cover Image, Volume 51, Issue 3. (June 2018) - Zhao, Dan; Li, Qianshun; Liu, Mengting; Ma, Wenjuan; Zhou, Tengfei; Xue, Changyue; Cai, Xiaoxiao
Abstract : The cover image, by Dan Zhao et al., is based on the Original Article Substrate stiffness regulated migration and invasion ability of adenoid cystic carcinoma cells via RhoA/ROCK pathway, DOI:10.1111/cpr.12442 .